Integration among Supply Chain Partners - Fajfer, Paweł (Integracja partnerów łańcucha dostaw, 2010)
Supply chain management enables the physical transfer of goods and information. During the transfer of information among business partners, in the logistics supply chain this information is often modified by them. Therefore, information systems of business partners must ensure the integration of the different elements of the logistics supply chain. In this article the question why should companies implement IT systems is answered, and benefits of e-commerce in SCM, and benefits of using GS1 standards are described.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 129-137
Keywords: ERP; SCM; GS1; EDI; information